The development of a community participatory model leading to the diamond level of health promotion school at Wut Saluck Nuea school, Nonthaburi province - Iemsawasdikul, Warinee; Moolsart, Sutteeporn; Potisupsuk, Cheunjit; Jawsungnern, Sumon; Saensuk, Pensri (Thai Journal of Nursing, 2020)
The objectives of this research and development were: 1) to study the participation of community and health behaviors of students; 2) to develop a community participatory model (CPM) leading to the diamond level of health promotion school; and 3) to investigate the implementation feasibility of the CPM to promote Wut Saluck Nuea school to be the diamond level of health promotion school. The sample were as follow: 1) Fifty four of students, teachers, parents and community representatives for focus group and six stakeholders of the development of health promotion school for in-depth interview; 2) Ten of developmental team for model development; 3) Thirty of students, parents, teachers, school administrators, professional nurse and community stakeholders for feasibility study. Research tools were questionnaires on 1) guideline for focus group and in-depth interview; health behaviors and community participation for the student; community participation for the parent; and the implementation feasibility. Data were analyzed by content analysis and descriptive statistics. The findings revealed that: 1) the students and the parents participated in the development of health promotion school at the high and moderate level respectively; the students had health behaviors and mental care and personal hygiene at the high level. 2) The CPM leading to the diamond level health promotion school comprised of 4 dimensions of participation as follows; (1) the decision making comprised of 1 strategy and 5 methods; (2) the implementation comprised of 3 strategies and 15 methods; (3) the benefits comprised of 1 strategy and 4 methods and (4) the evaluation comprised of 1 strategy and 3 methods. 3) The implementation feasibility of the CPM in total and all items was at the high level.